Analisis Kepribadian Tokoh Utama dalam Novel Dangerous Romance Karya Daisy Ann: Kajian Psikologi Sastra - Raihan, Muhammad; Damayanti, Welsi (Aksara: Jurnal Bahasa dan Sastra, 2024)
This research is based on the selfish side that exists in the personality of the main character in Daisy Ann's novel Dangerous Romance which can be studied more deeply with Sigmund Freud's psychoanalytic theory. The research method used is descriptive-qualitative, with the aim of describing the personalities of the main characters, Maura and Benny Arliansyah, based on the concepts of Id, Ego, and Superego. The research data are sentences quoted directly from the novel Dangerous Romance by Daisy Ann. The identity of Maura's personality includes the desire to possess, the desire for Ben's attention, the desire to be a good wife, and the desire to be a friend of Ben. The ego of the Maura personality encompasses selfishness, ambition, and reluctance to surrender, attention, openness, and jealousy. The superego in Maura's individuality involves the awareness of his egoism and the consciousness of releasing Ben. As for the superego that is seen in him, it is his awareness of his fault. These personality concepts can be used as a life lesson that one's selfishness can destroy everything. This finding is also a sign that Sigmund Freud's psychoanalytic theory can be used as a primary foundation in the study of novel literature so that it can be reimplemented in other literary works, whether drama or scripture.Keywords: Dangerous Romance, Psychoanalysis, Main Characters